Validity of Neuropsychological Testing in Young African Children Affected by HIV - Chernoff, Miriam C.; Laughton, Barbara; Kamthunzi, Portia; Kabugho, Enid; Joyce, Celeste; Jean-Philippe, Patrick; Boivin, Michael J. (Journal of pediatric infectious diseases, 2018)
Western-constructed neuropsychological tests have been used in low- and middle-income countries to assess the impact of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) and other chronic illnesses. We explore using such instruments cross-culturally in a sub-Saharan African setting. IMPAACT P1104S was a 2-year observational study performed at six clinical sites (South Africa—three sites, Malawi, Uganda, and Zimbabwe) to assess and compare neuropsychological outcomes in three cohorts of children between the ages of 5 and 11 years: HIV-infected (HIV), HIV-exposed but uninfected (HEU), and HIV unexposed and uninfected (HU). Descriptive statistics compared sociodemographic characteristics among children at sites. Instruments included the Kaufman Assessment Battery for Children, 2nd edition (KABC-II) cognitive ability, Test of Variables of Attention (TOVA) attention/impulsivity, Bruininks–Oseretsky Test of Motor Proficiency, 2nd edition (BOT-2) motor proficiency tests, and Behavior Rating Inventory for Executive Function (BRIEF) executive function problems. Test characteristics were assessed using intraclass and Spearman's nonparametric correlations, linear regression, and principal factor analyses. Of the 611 participants, 50% were males and mean age ranged from 6.6 to 8 years. In Malawi, Uganda, and Zimbabwe, substantial proportions of families lived in rural settings in contrast to the South African sites. Intraclass correlation coefficients between weeks 0 and 48 were highest for the KABC scores, ranging between 0.42 and 0.71. Correlations among similar test domains were low to moderate but significant, with positive correlation between KABC sequential and TOVA scores and negative correlation between BRIEF and KABC scores. TOVA response time scores correlated negatively with the BOT-2 total points score. Strong and significant associations between individual measures of growth, disability, and development with all test scores were observed. Performance-based measures were markedly lower for HIV compared with HEU and HU participants, even after controlling for age, sex, and site. Factor analyses confirmed the underlying theoretical structure of the KABC scaled item scores. The KABC, TOVA, BRIEF, and BOT-2 were valid and reliable tools for assessing the neuropsychological impact of HIV in four sub-Saharan African countries.
Keywords: Reliability; Pediatric HIV; Neuropsychological testing